Hubungan Personal Branding @nanakoot di TikTok dengan Brand Awareness Pizza Ranjang - Huwaida, Aqilah Zafira; Nugroho, David Rizar (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
Currently, many social media including TikTok make it easy for a brand to do digital marketing to reach audiences and other specific goals. The same is true for Pizza Ranjang which wants brand awareness created by consumers to increase. This is in line with Pizza Ranjang's vision and mission that it will continue to collaborate and build broader relationships with external parties, one of which is to the audience through collaboration with key opinion leaders (KOL). KOL can increase and attract audiences to watch content created by relying on their personal branding. This is one of the important strategies in marketing communications. This study aims to analyze the relationship between the personal branding of the TikTok account @nanakoot as a key opinion leader and Pizza Ranjang's brand awareness. The method used is quantitative descriptive correlational with a purposive sampling technique of 156 respondents obtained from the Slovin formula where the population is known, namely the followers of the TikTok account @nanakoot as many as 8,700,000. Data collection in this study used a survey via Google Form and was analyzed using the Spearman Rank correlation test via SPSS version 30. The results showed that there was a fairly positive and significant relationship (r = 0.444, p <0.001) between @nanakoot's personal branding and Pizza Ranjang brand awareness.